2013
DOI: 10.5194/acpd-13-13541-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Arctic Summer Cloud-Ocean Study (ASCOS): overview and experimental design

Abstract: The climate in the Arctic is changing faster than anywhere else on Earth. Poorly understood feedback processes relating to Arctic clouds and aerosol-cloud interactions contribute to a poor understanding of the present changes in the Arctic climate system, and also to a large spread in projections of future climate in the Arctic. The problem is exacerbated by the paucity of research-quality observations in the central Arctic. Improved formulations in climate models require such observations, which can o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 162 publications
0
66
0
Order By: Relevance
“…Subsequently, Leck and Bigg (1999) used the PBL structure and the vertical distribution of particles during nucleation events to show that, if the newly formed particles did come from above, they had to come from a level less than 140 m above the surface, and not from the free troposphere. Particles with sizes below 50 nm in diameter during four Arctic icebreaker expeditions, in the summers of 1991 , 1996 , 2001 Tjernström et al, 2004) and 2008 (Paatero et al, 2009;Tjernström et al, 2013), have been shown to be produced by in situ fine-particle sources over the high Arctic…”
Section: P Kupiszewski Et Al: Vertical Profiling Of Aerosol Particlmentioning
confidence: 99%
“…Subsequently, Leck and Bigg (1999) used the PBL structure and the vertical distribution of particles during nucleation events to show that, if the newly formed particles did come from above, they had to come from a level less than 140 m above the surface, and not from the free troposphere. Particles with sizes below 50 nm in diameter during four Arctic icebreaker expeditions, in the summers of 1991 , 1996 , 2001 Tjernström et al, 2004) and 2008 (Paatero et al, 2009;Tjernström et al, 2013), have been shown to be produced by in situ fine-particle sources over the high Arctic…”
Section: P Kupiszewski Et Al: Vertical Profiling Of Aerosol Particlmentioning
confidence: 99%
“…The quality of the samples was additionally monitored using various combustion tracers and wind speed -and direction -thresholds: provided that the wind was within ±70 • of the direction of the bow and stronger than 2 m s −1 , no ship pollution reached the sample inlets. Further details of the location and properties of air intakes and instruments, position on the ship, pumping arrangements and precautions to exclude contaminated periods can be found in Leck et al (2001) and in Tjernström et al (2013).…”
Section: Atmospheric Sampling Of Aerosol Particles Onboard Shipmentioning
confidence: 99%
“…The Sun was continuously above the horizon of the expedition. For further cruise details see Paatero et al (2009) and Tjernström et al (2013).…”
Section: Locationmentioning
confidence: 99%
“…During August of 2008, the Swedish ice breaker Oden served as a drifting base camp for the Arctic Summer Cloud Ocean Study (ASCOS, Tjernström et al, 2013). The vessel headed north from Svalbard with a goal to spend as much time as possible in the central Arctic ice pack.…”
Section: Ascosmentioning
confidence: 99%
“…In the current work, we evaluate some of the tools described above using measurements obtained during the Arctic Summer Cloud Ocean Study (ASCOS, Tjernström et al, 2013). The ASCOS data set provides us with a unique opportunity to assess the performance of models at high latitudes.…”
Section: Introductionmentioning
confidence: 99%